Distribuição de palmeiras (arecaceae) ao longo de gradientes ambientais no baixo interflúvio purusmadeira, Brasil - Sousa, Thaise Emilio Lopes de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
In order to study the relationship between soil, litter and palm community composition at the mesoscale, species surveys were conducted in 40 plots of terra-firme forest and litter depth, soil texture and soil fertility were determined. All sites were located on a weakly incised fossil floodplain that now forms the interfluve between the lower reaches of the Purus and Madeira Rivers (Brazil). The inventory plots covered a soil texture gradient ranging from 38 to 74 percent silt, exchangeable bases varying from 0.11 to 0.53 cmol.kg-1 and litter depth between 4.9 and 19.4 cm. The palm species composition was strongly affected by the litter thickness, soil texture and fertility at the mesoscale and these environmental variables together explained up to 49% of floristic variation. This supports the theory that deterministic processes related to the environmental conditions within terra-firme are involved in explaining community structure at the mesoscale. Different edaphic factors affected the composition of different life stages. Soil fertility was more important for the juveniles and soil texture for the adults. For the community as a whole, soil texture was more important than fertility in determining species composition. In areas where the fertility varies little, soil texture may be associated with a hydrological gradient which structures the palm community. The effects of edaphic components on plant community structure have been reported previously for different plant groups. The strong effect of litter depth at the mesoscale, however, has not been highlighted. Taller palm communities were associated with deeper litter, suggesting that the amount of litter affects both forest structure and composition. The qualitative composition (presence/absence) of juvenile palms was affected by litter depth, demonstrating the fundamental importance of this factor for short-term plant establishment. Litter thickness may have direct or indirect effects on the species distribution, community composition and forest structure, and thus other plant or animal groups may be influenced by litter in the studied area. The width of the environmental gradients occupied by juveniles and by adults were similar, suggesting that for narrow environmental gradients mass effect is less evident.
Keywords: Palmeiras; Floresta tropical; Rodovia BR-319